Financing strategy to support a product development of aluminium finished goods (case study: PT. XYZ) - Donny Marshal; Uke Marius Siahaan (President University, 2021)
Nowadays, the use of wood materials for construction is starting to be reduced because it can cause global warming due to cutting down forests. There are changes in the construction used aluminium materials such as frames and doors. There is an increasing demand for aluminium products which is an opportunity for companies to develop products. Currently the company manufactures aluminium profile products (semi-finished goods), so the company needs to develop aluminium finished goods products to increase profits and brand image. The investment required by the company is 11,232,000,000 rupiah to develop aluminium finished goods products. This research uses financial feasibility study, then selects the best investment financing. Net Present Value (NPV), Profitability Index (PI), Internal Rate of Return (IRR), Payback Period (PP), and Return on Investment (ROI) are used as variables for determining investment. There are four financing alternatives, including internal financing, bank, leasing and IPO. The results showed that bank financing provided the highest NPV and ROI with an NPV value of 1,546,356,903, Profitability Index (PI) of 1.14, Internal Rate of Return (IRR) of 10.09%, Payback Period of 4 years 1 month, Return on Investment (ROI) of 28.24% and US Index of 4.71. Thus, the results of this research recommend using bank financing for investment in product development.